2009
DOI: 10.1111/j.1365-2400.2009.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of gastrically and surgically implanted telemetry transmitters in shovelnose sturgeon

Abstract: Transmitter retention and the effects gastrically and surgically implanted telemetry transmitters had on condition and mortality of shovelnose sturgeon, Scaphirhynchus platorhynchus (Rafinesque), >450-mm fork length were examined. Four, 35-day trials were conducted with approximately equal numbers of control fish, fish receiving dummy transmitters gastrically and fish receiving dummy transmitters surgically. Four sturgeon expelled gastrically implanted transmitters during the observation period. Two mortalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…; Neely et al. ), our experiment showed no such short‐term impacts. Tagging effect studies often occur over a shorter time period and consist of frequent sampling events (e.g., Moore et al.…”
Section: Discussioncontrasting
confidence: 53%
“…; Neely et al. ), our experiment showed no such short‐term impacts. Tagging effect studies often occur over a shorter time period and consist of frequent sampling events (e.g., Moore et al.…”
Section: Discussioncontrasting
confidence: 53%
“…We are unaware of any studies indicating that transmitter failure is likely. Tank studies of sturgeons have generally shown that tag expulsion is unlikely (Collins et al 2002;Neely et al 2009; although see Boone et al 2013).…”
Section: Atlantic Sturgeon Survival In Four River Basinsmentioning
confidence: 99%
“…generally do not feed during the freshwater spawning migration. For these large fish, gastric implantation is usually preferred to surgical or external attachment, as the radio transmitters can be inserted quickly with minimal fish handling (Bridger and Booth 2003;Neely et al 2009;Thiem et al 2011). In deciding which attachment method to use, it is important for researchers to consider the stage of migration at the time of tagging.…”
mentioning
confidence: 99%